Improving Students’ Learning Outcome Through Team Quiz Model With Number Bag Media at First Grade SDN Koto Baru - Vera, Yanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This study aims to improve student learning outcomes in mathematics by using the Team Quiz Learning Model with the Help of Numbers Pocket Media in Grade I.a students of SD Negeri 01 Koto Baru, Koto Baru District, Dharmasraya Regency. This type of research is Classroom Action Research (CAR), using the Kemmis and McTaggart model which includes planning, action and observation, as well as reflection in each cycle. The subjects in this study were students of class I.a SD Negeri 01 Koto Baru, totaling 31 students. Data collection techniques using observation, tests, and documentation. Data were analyzed quantitatively and qualitatively. The success indicator is 75% of the number of students who have reached the specified KKM, which is 70. The results show that the application of the Team Quiz Learning Model With the Help of Numbers Pocket Media in Class I.a Students of SD Negeri 01 Koto Baru, Koto Baru District, Dharmasraya Regency. When no action has been given, the mathematics learning score of grade 1 students at SD Negeri 01 Koto Baru is 58.06% of students who reach the KKM. In the first cycle of action activities there was an increase, as many as 77.21%, students who reached the KKM. And in the second cycle as much as 90.32% managed to achieve the value of completeness